Konservasi Makam Keramat Solear Sebagai Warisan Budaya - Zahra, Nur Amalia; Koimah , Siti Mariyatul; Nugroho, Febrian Tri; Ardiansyah, Septian Syahnam; Pricillia, Kezia (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
This research explores the challenges and potential in preserving the Sacred Solear Tomb as a valuable cultural heritage. Through field studies, interviews, and data analysis, we identified physical damage to the site and the significance of this tomb in the cultural and religious context of the local community. In addressing these challenges, we propose a series of concrete steps, including physical restoration, education and public awareness campaigns, involving the younger generation, collaborating with conservation institutions, policy development, and ongoing monitoring. Through these efforts, we hope to ensure that the Sacred Solear Tomb remains a vibrant and relevant part of culture and religious life while preserving its physical integrity for future generations. The preservation of this cultural heritage is our commitment to safeguarding an invaluable legacy for our culture.